A STUDY ON A RHETORICAL APPROACH TO EFFECTIVE COMMUNICATION TO RESOLVE CONFLICTS AT INDUSTRIES - Moorthy, D; Ghosal, Madhumita (PEOPLE: International Journal of Social Sciences, 2017)
Language has the power to pacify or create disputes and barriers among humans. This is because one’s language is impregnated with his expressions, opinions and intentions. The literal meaning of words used by the speaker may vary from the intended meaning which may lead to conflicts. An industry is an organization where people from various fields work together for one cause. When these individuals with varied opinions work together, they would definitely confront with differences in opinions which may lead to conflicts at industries. They need good coordination and cooperation to achieve their common goal of attaining profits to their industry. Though experts have proposed number of theories to resolve conflicts at industries,effective communication is the only key to diffuse them non-violently. A Rhetorical Approach to the communication would enhance its effectiveness in the process of conflict resolution at industries. Aristotle’s Rhetoric consists of three appeals, i.e. Logos, Ethos & Pathos.Aristotle proclaimed that with a right combination of these three appeals of Rhetoric a speech can be made more effective during conflict resolution at industries. This paper aims to identify some of the effective applications of the three appeals of Rhetoric to resolve conflicts at industries.